2015
DOI: 10.1098/rsta.2015.0146
|View full text |Cite
|
Sign up to set email alerts
|

Feedbacks, climate sensitivity and the limits of linear models

Abstract: The term 'feedback' is used ubiquitously in climate research, but implies varied meanings in different contexts. From a specific process that locally affects a quantity, to a formal framework that attempts to determine a global response to a forcing, researchers use this term to separate, simplify and quantify parts of the complex Earth system. We combine new model results with a historical and educational perspective to organize existing ideas around feedbacks and linear models. Our results suggest that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
125
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(130 citation statements)
references
References 125 publications
3
125
0
2
Order By: Relevance
“…Consequently, the T intercept (N = 0) for the first 20 years of the simulation underestimates the actual warming of the model. Over longer timescales, the slope of the regression line becomes less negative, implying that the sensitivity of the climate system to the forcing increases Gregory et al, 2004;Knutti and Rugenstein, 2015). This non-linearity has been found to be particularly apparent in cloud feedback parameters, in particular shortwave cloud feedback processes .…”
Section: Gregory Plotsmentioning
confidence: 97%
“…Consequently, the T intercept (N = 0) for the first 20 years of the simulation underestimates the actual warming of the model. Over longer timescales, the slope of the regression line becomes less negative, implying that the sensitivity of the climate system to the forcing increases Gregory et al, 2004;Knutti and Rugenstein, 2015). This non-linearity has been found to be particularly apparent in cloud feedback parameters, in particular shortwave cloud feedback processes .…”
Section: Gregory Plotsmentioning
confidence: 97%
“…R and T s change over time. In addition, some studies suggest that the heat uptake by the ocean is also time dependent and even λ is not a constant parameter (e.g., Knutti and Rugenstein, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Crucifix, 2006;Hargreaves et al, 2007;Yoshimori et al, 2011;Yin and Berger, 2012;Caballero and Huber, 2013;Goldner et al, 2013;Kutzbach et al, 2013;Meraner et al, 2013) and palaeodata-based (PALAEOSENS-Project Members, 2012;von der Heydt et al, 2014) approaches have already indicated that S varies for different background climates; see also a recent review of Knutti and Rugenstein (2015) on the limits of linear models to constrain climate sensitivity. The majority of simulation studies shows a rise in climate sensitivity for a warmer background climate.…”
mentioning
confidence: 99%